Anti-interleukin-5 therapy (mepolizumab) in life-threatening asthma attack: A case-based discussion. (2019) - Tello, Khodr; Hoffmann, Andreas; Beutel, Björn; Greulich, Timm; Vogelmeier, Claus Franz; Richter, Manuel Jonas; Kuhnert, Stefan; Böselt, Tobias; Alter, Peter; Holland, Angelique; Idzko, Marco; Buhl, Roland; et al.
Abstract: We report about a case of a compassionate off-label use of the anti-interleukin-5-agent mepolizumab in a ventilated patient with life-threatening asthma attack in eosinophilic asthma. The patient suffered from severe eosinophilic asthma and was transmitted to our hospital with an asthma attack and a life-threatening respiratory state under ventilation. Since high dose steroids had not yielded a sufficient respiratory improvement mepolizumab was administered subcutaneously. After administration of mepolizumab respiratory state and ventilation parameter improved significantly. Two days after administration the patient was weaned could be extubated 8 days later and recovered completely from the asthma attack. The presented clinical case is suggestive of future clinical trials or registry studies to evaluate potential clinical benefits of anti-interleukin-5 treatment in patients with severe exacerbations of eosinophilic asthma.